Effect of Electrode and Electrolyte Thicknesses on All-Solid-State Battery Performance Analyzed With the Sand Equation - Devaux, Didier; Leduc, Hugo; Dumaz, Philippe; Lecuyer, Margaux; Deschamps, Marc; Bouchet, Renaud (Frontiers in Energy Research, 2020)
The energy conversion and storage are great challenges for our society. Despite the progress accomplished by the Lithium(Li)-ion technology based on flammable liquid electrolyte, their intrinsic instability is the strong safety issue for large scale applications. The use of solid polymer electrolytes (SPEs) is an adequate solution in terms of safety and energy density. To increase the energy density (resp. specific energy) of the batteries, the positive electrode thickness must be augmented. However, as for Li-ion liquid electrolyte, the cationic transference number of SPEs is low, typically below 0,2, which limits their power performance because of the formation of strong gradient of concentration through the whole battery. A compromise between the energy density and the power has to be found. The goal of this study is to propose a simple methodology to optimize the thickness of the SPE and the positive electrode based on charge transport parameters, which allows to determine the effective limiting Li+ diffusion coefficient. First, we develop an efficient method to rapidly establish the battery power performance, then by using an approach based on Sand theory, we determine the limiting current density which allows to obtain a unique mother curve of the capacity as a function of the current density whatever the electrode and electrolyte thicknesses. Finally, the effective limiting diffusion coefficient is obtained which in return allows to design the best electrode depending on electrolyte thickness.